Effectiveness of video-assisted teaching module on knowledge and attitude of college students on HIV/AIDS - Chitra, A.Felicia; Kalavathi; Dash, Manjubala (Indian Journal of Nursing Sciences, 2024)
Aim: To assess the existing knowledge and attitude regarding HIV/AIDS among the college students. To assess the effectiveness of VATM on the knowledge and attitude regarding HIV/AIDS among the college students. Materials and Methods: Pre and posttest with control group design was adopted to assess the effectiveness of Video teaching towards knowledge and attitude regarding HIV/AIDS among the 400 (200 in control and 200 in experimental group) college students. Data was collected by a structured questionnaire on knowledge and attitude about HIV/AIDS. Results: The distribution of the demographic characteristics of college students in experimental and control group. In both, the experimental and control group 58% and 53.5% of the students were in the age group of 19 to 20 years respectively. Overall knowledge regarding HIV/AIDS among the college students in the experimental group had significantly improved after the intervention than that of the control group. Comparison of pre and posttest mean attitude score among the college students towards HIV/AIDS in the experimental group and control group highlights that in the experimental group the mean attitude score increased from 57.15 in the pretest to 67.33 in the posttest after intervention. Conclusion: Video teaching module was shown effective to improve knowledge and attitude of the college students regarding HIV/AIDS